Penilaian Kualitas Informasi Dokumen Rekam Medis Rawat Jalan - Cindy Kusuma Dewi (Universitas Airlangga, 2017)
Performance evaluation was showed that average service time from January to October 2016 was 35.56 minutes. The average service time ensuring provision of medical records of outpatients was under targets because the standard of service time of the Minister of Health No. 129 at 2008 is <10 minutes. This research aimed to determine the information quality of medical record documents outpatients as helped efforts to improve the information quality of medical record documents. This was a descriptive study with cross-sectional design. Data was collected through observation outpatient medical record on December. The samples consisted 115 medical record documents. The sampling method used was random sampling. Variable used by researchers was the quality dimensions of The Product and Service Performance for Information Quality Model. The results showed the dimensions free of error of 68.33%, dimensions of concise representation of 58.44%, and the dimensions of completeness by 55.56%, and dimensions of consistent representation of 52.22%. Based on research result, average score of information quality assessment were good enough. Recommendation for Medical Record Departementbased on research results was made guidelines or standard operating procedures could be used to increase the quality of medical record documents. Keywords: assessment, dimension, information quality, Medical Record Document,outpatient